Everyday crime, criminal justice and gender in early modern Bologna - Muurling, Sanne, 1987- (Crime and city in history ;, 2021)
"Female protagonists are commonly overlooked in the history of crime; especially in early modern Italy, where women's scope of action is often portrayed as heavily restricted. This book redresses the notion of Italian women's passivity, arguing that women's crimes were far too common to be viewed as an anomaly. Based on over two thousand criminal complaints and investigation dossiers, Sanne Muurling charts the multifaceted impact of gender on patterns of recorded crime in early modern Bologna. While various socioeconomic and legal mechanisms withdrew women from the criminal justice process, the casebooks also reveal that women - as criminal offenders and savvy litigants - had an active hand in keeping the wheels of the court spinning"--